PO48 | Thrombotic risk evaluation and thrombophilia testing in beta-thalassemia patients: a retrospective cohort analysis from a reference regional center (Bleeding, Thrombosis and Vascular Biology)
Background: β-thalassemia (βT) is a group of inherited hemoglobin synthesis disorders, characterized by defective β-chain synthesis. Clinical complications related to hemostasis, including pulmonary hypertension, venous thromboembolism (VTE), and ischemic arterial events, occur in βT with a prevalence ranging from 1.1% to 5.3%. The exact cause of the hypercoagulable state in βT patients remains unclear, though several factors have been advocated. Thrombophilia might contribute to VTE in βT, but studies do not show an increased frequency of inherited thrombophilia conditions in βT patients. However, more well-structured studies are needed to reach definitive conclusions.